Validity and reliability of patient reported outcomes measurement information system computerized adaptive tests in systemic lupus erythematous. (November 2021) - Moazzami, Mitra; Katz, Patricia; Bonilla, Dennisse; Engel, Lisa; Su, Jiandong; Akhavan, Pooneh; Anderson, Nicole; Tayer-Shifman, Oshrat E; Beaton, Dorcas; Touma, Zahi
Background: The evaluation of Patient Reported Outcomes Measurement Information System (PROMIS) computerized adaptive test (CAT) in adults with systemic lupus erythematous (SLE) is an emerging field of research. We aimed to examine the test–retest reliability and construct validity of the PROMIS CAT in a Canadian cohort of patients with SLE. Methods: Two hundred twenty-seven patients completed 14 domains of PROMIS CAT and seven legacy instruments during their clinical visits. Test–retest reliability of PROMIS was evaluated 7–10 days from baseline using intraclass correlation coefficient (ICC (2; 1)). The construct validity of the PROMIS CAT domains was evaluated against the commonly used legacy instruments, and also in comparison to disease activity and disease damage using Spearman correlations. A multitrait-multimethod matrix (MMM) approach was used to further assess construct validity comparing selected 10 domains of PROMIS and SF-36 domains. Results: Moderate to excellent reliability was found for all domains (ICC [2;1] ranging from lowest, 0.66 for Sleep Disturbance and highest, 0.93 for the Mobility domain). Comparing seven legacy instruments with 14 domains of PROMIS CAT, moderate to strong correlations (0.51–0.91) were identified. The average time to complete all PROMIS CAT domains was 11.7 min. The MMM further established construct validity by showing moderate to strong correlations (0.55–0.87) between select PROMIS and SF-36 domains; the average correlations from similar traits (convergent validity) were significantly greater than the average correlations from different traits. Conclusions: These results provide evidence on the reliability and validity of PROMIS CAT in SLE in a Canadian cohort.